Biomarkers to Assess the Targeting of DNA Repair Pathways to Augment Tumor Response to Therapy - Nowsheen, S.; C. Whitley, A.; S. Yang, E. (Current Molecular Medicine, 2012)
Hyper-activation of DNA repair pathways can enable tumor cells to survive DNA damage. Therefore, targeting specific DNA repair pathways might prove efficacious for cancer therapy. The advent of personalized therapy necessitates novel biomarkers to assess tumor response to therapy. Biological indicators are vital in the field of cancer research and treatment. The focus of this review is on the DNA repair machinery as an emerging target for enhancement of therapy. Additionally, DNA damage and repair biomarkers for prognosis in different types of cancer will be discussed. The application of biomarkers to assess tumor response to therapy based on targeting DNA repair pathways can potentially improve patient quality of life and aid in treatment design.
Keywords: genomic instability